IPTEKS OPERASIONALISASI PENGGUNAAN APLIKASI LED (LOSS EVENT DATABASE) PADA PT BANK SULUTGO CABANG PEMBANTU BAHU - Samsudin, Mahdiani Erita; Rundengan, Fanda (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT bank SULUTGO is one of the companies who are moving in the banking field. One of the best ways to know every branch of branch from pt bank sulutgo is applying the database loss event that may be able to help the process of walking way with good conditions. Application loss event database (LED) is a web-based application used to help banks in inventory of losses damaged or needed by banks and the potential of bank losses and planning of risk response related to operational risk management. Trusted operations.Data of losses are very important for connecting bank risk estimates to experiences of loss with risk management and control decisions.Keywords : Application Loss Event,Risk And Control Decisions Management